1971
DOI: 10.1063/1.1685352
|View full text |Cite
|
Sign up to set email alerts
|

A Square Wave Dissociation Field Effect Pulse Generator for Use with Spectrophotometric Detection

Abstract: A 50 kV square wave pulse generator and associated control circuitry for use in spectrophotometric dissociation field effect experiments has been constructed. The design differs from previous pulse generators in that cumbersome delay cables are not used. A 0.005 μF plastic capacitor is charged to a voltage adjustable from 30 to 52 kV. When the desired voltage is reached, a triggered spark gap is fired, connecting the capacitor to the chemical cell. At a preset delay time, continuously adjustable from 0 to 29 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…2)] + kd° (5) the maximum ionic strength was about 500 µ , the Debye-Hückel limiting law is a good approximation. In this treatment the activity coefficient of a species is determined by the magnitude of its electrical charge.…”
Section: Resultsmentioning
confidence: 88%
“…2)] + kd° (5) the maximum ionic strength was about 500 µ , the Debye-Hückel limiting law is a good approximation. In this treatment the activity coefficient of a species is determined by the magnitude of its electrical charge.…”
Section: Resultsmentioning
confidence: 88%
“…f Ionic strength of the sample solution. 8 Total concentration of hydrogen ion and sample acid anion calculated from pKa = 3.47 in the case of Methyl Orange and pKa = 5.00 for Methyl Red.…”
Section: Discussionmentioning
confidence: 99%
“…Sample solutions evidenced a pH constant to within ±0.03 pH units when tested prior to and immediately succeeding the E-jump experiment (a time interval of up to 30 min). The electric field jump (E-jump) relaxation method apparatus used was basically identical with that described by Olsen, et al 8 The major modification involved the use of a digital delay trigger generator having a time base referenced to a 10-MHz quartz crystal. This allows for more accurate control of the square, high-voltage pulse width.…”
Section: Introductionmentioning
confidence: 99%
“…The usual kinetic analysis yields two simultaneous differential equations11 from which the two relaxation times can be obtained by evaluating the determinant with S = a n +022 and P = 011022 -a 12a 21-Under the conditions that kV2, k2\ » fe23, ^32 it is evident that a 11 » a 2 2 and 012 >>021-Thus the fast relaxation time becomes rfast'! = «U + «22 ~«11 = fel2([PhH-] + [OH-]) + kn (6) and slow one Low concentrations, and the fact that k 12 and k2i are diffusion controlled simplifies the last term in eq 7 to k23, resulting in Tglow"1 ~^32 (8) In this case, and if the observation is done on species Ph2~• aq, only the slow relaxation can be observed which is concentration independent. To observe both relaxations, the concentration of the intermediate Ph2~• aq or that of PhH~has to be followed, which, however, do not absorb in the visible range of the spectrum.…”
Section: *33mentioning
confidence: 99%
“…Previously, it has been suggested that the highly alkaline ice may represent an extreme in effective matrix polarity. [2][3][4][5][6][7][8] In this work we have studied excess electrons in a different aqueous glass, 5 M K2C03. By photoconductivity and optical bleaching studies we have found that trapped electrons of at least two different types are The Journal of Physical Chemistry, Vol.…”
Section: Introductionmentioning
confidence: 99%